1960
DOI: 10.1063/1.1731496
|View full text |Cite
|
Sign up to set email alerts
|

Critical Opalescence of Polystyrene in Cyclohexane

Abstract: In a recent publication on critical opalescence it was shown that, for a binary liquid mixture of critical concentration, measurements of the angular dependence of scattered intensity at small temperature distances above the critical temperature can be related to the range of molecular forces.' This concept has been applied to polymer solutions. The range of molecular forces and the critical temperature of solutions of polystyrene of different molecular weights in cyclohexane have been reported.2 It was found … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
27
0

Year Published

1961
1961
1999
1999

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 98 publications
(30 citation statements)
references
References 10 publications
3
27
0
Order By: Relevance
“…(12) In subsection 3.3.1 were discussed experiments in the region of critical opalescence (polymer solutions), their results are rather inconsistent, but some of them (including Debye's et al, 1960b) corroborates Equation 12.…”
Section: Critical Opalescencementioning
confidence: 98%
See 3 more Smart Citations
“…(12) In subsection 3.3.1 were discussed experiments in the region of critical opalescence (polymer solutions), their results are rather inconsistent, but some of them (including Debye's et al, 1960b) corroborates Equation 12.…”
Section: Critical Opalescencementioning
confidence: 98%
“…Measurements in the precritical region and calculations from Equation 26 have shown a significant decrease in coil size in comparison with the sizes of the coils at the 0 temperature and infinite dilution ( c -+ 0) (Debye et al, 1960bNesterov, 1966ab, 1967a;Eskin, 1973).…”
Section: 3mentioning
confidence: 99%
See 2 more Smart Citations
“…(1 -4c) system has been provided by Krigbaum and Geymer (9) who found that where m,, and m, are the weight and z-average relative chain lengths of a polymer component [15] (5) data and 0.093 from that of Debye and his co-workers (6). Debye used sharp fractions of anionically polymerized polystyrene which reduces the heterogeneity correction to less than 1% but no correction can be applied to the Flory-Schultz data as the molecular weight distribution of each sample is unknown.…”
mentioning
confidence: 99%